Development of Interactive Multimedia Narrative Text (Medtenar) and Its Effectiveness in Enhancing Elementary Students’ Reading Comprehension - Lintang Ardipratiwi; Andarini Permata Cahyaningtyas (Jurnal Paedagogy, 2026)
This study aims to describe the development of an interactive multimedia narrative text (Medtenar) for teaching narrative text reading comprehension to fourth-grade elementary students and to evaluate its feasibility and effectiveness. The research employed a Research and Development (R&D) method using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). Participants included seven fourth-grade students in a one-on-one pilot test at SDN Podorejo 01 and 25 fourth-grade students in a field test at SDN Bringin 01. Data were collected through expert validation sheets for media and material/language content, student and teacher response questionnaires, and reading comprehension tests administered as pretests and posttests. Data analysis included: (1) feasibility assessment using Aiken’s V to determine expert validity, (2) practicality assessment through descriptive percentage scores from student and teacher questionnaires, and (3) effectiveness assessment using the Shapiro–Wilk normality test, paired-samples t-tests for pretest–posttest differences, and normalized gain (N-gain) to measure learning improvement. Validation results indicated that Medtenar is highly feasible, with Aiken’s V values of 0.977 (media experts) and 0.952 (material and language experts). Effectiveness testing showed improvements in reading comprehension, with N-gain scores of 0.6164 (pilot test) and 0.5997 (field test), both categorized as moderate. These findings suggest that Medtenar is a feasible and moderately effective learning medium for enhancing narrative text reading comprehension and is recommended to support Grade 4 learning under the Merdeka Curriculum and deep learning framework.